Meta-QTL Analysis and Genes Responsible for Plant and Ear Height in Maize (Zea mays L.) - Xin Li; Xiaoqiang Zhao; Siqi Sun; Kejin Tao; Yining Niu (Plants)
Plant height (PH) and ear height (EH) are closely related to dense planting characteristics and lodging resistance of maize (Zea mays L.). Increasing the planting density will lead to changes in the structural characteristics of maize plants, such as reduced stem length and stem strength, thereby influencing their yield and quality. Therefore, analyzing the genetic basis of PH and EH in maize can provide valuable information for cultivating ideal plant types with suitable PH and EH. This study aims to identify stable genomic regions and candidate genes associated with PH and EH in maize through Meta-QTL (MQTL) analysis. A total of 187 original QTLs were collected from 13 published articles on QTL localization related to maize PH and EH. A high-density consistency map with a total length of 6970.00 cM was constructed, and 152 original QTLs were successfully projected into the consistency map. The remaining 35 QTLs could not be projected onto the consistency map, which may be attributed to a lack of common markers between the original and consistency map or to the QTL exhibiting low phenotypic variance explained (PVE), resulting in large confidence intervals (CIs). Then, 29 MQTLs were identified on 10 chromosomes via meta-analysis. Among them, the three identified MQTLs, i.e., MQTL4-1, MQTL4-2, and MQTL6-1, were specifically controlled by maize EH. Further analysis achieved 188 candidate genes in all MQTL intervals, which were related to maize plant development and morphogenesis. Meanwhile, the gene ontology (GO) enrichment analysis revealed that these candidate genes were involved in 77 GO annotations. These findings thus will help us better understand the molecular genetic basis of maize PH and EH under various environments, and thereby achieve an increased yield with maize dense planting breeding.